2008
DOI: 10.1088/0022-3727/41/13/135006
|View full text |Cite
|
Sign up to set email alerts
|

Observation of room temperature ferromagnetism in Mn–Fe doped ZnO

Abstract: A room temperature ferromagnetic Fe doped ZnO bulk sample has been synthesized by co-doping 2 at% Mn with 2 at% Fe in ZnO. The final firing temperature for the preparation of the Zn0.96Mn0.02Fe0.02O sample is the same as the final firing temperature for the preparation of the Zn0.98Mn0.02O sample and in this case it is found to be 490 °C. It has been found that room temperature ferromagnetism in Zn0.96Mn0.02Fe0.02O is a factor of 1.6 times more than that observed in Zn0.98Mn0.02O samples. The size of the satur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Since Fe is popular as a contributor of higher individual magnetic moment, co doping with Fe would be an equally interesting issue to be addressed. Moreover, it has been found that chemically Fe can be co doped in ZnO effectively along with Mn and Co [14][15][16] for higher ferromagnetism (∼10 À 2 emu/g).…”
Section: Introductionmentioning
confidence: 99%
“…Since Fe is popular as a contributor of higher individual magnetic moment, co doping with Fe would be an equally interesting issue to be addressed. Moreover, it has been found that chemically Fe can be co doped in ZnO effectively along with Mn and Co [14][15][16] for higher ferromagnetism (∼10 À 2 emu/g).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many experimental studies on magnetic and non-magnetic doped ZnO films showing room temperature ferromagnetism, the origin of ferromagnetism is still strongly debated in transition metal (TM)-doped oxide DMSs such as ZnO-based DMS [16][17][18]. Early studies proposed that a free carrier mediated mechanism was responsible for the ferromagnetic behavior [19].…”
Section: Introductionmentioning
confidence: 99%
“…19 Sapphire has been widely used as substrate due to the small mismatch ͑2%͒ between ͑0001͒ oriented ZnO and Al 2 O 3 ͑1120͒ substrates. In addition to cobalt, other 3d transition elements have also been used for doping, including Mn, 5,15,[20][21][22] Ni, 5,11,15 V, 11,15,23 Cr, 5,11 and also Fe. 5,11,15,24 Various solubility limits for Co in ZnO were reported by different groups.…”
Section: Introductionmentioning
confidence: 99%